2016
DOI: 10.1137/15m1032740
|View full text |Cite
|
Sign up to set email alerts
|

Polar Gaussian Processes and Experimental Designs in Circular Domains

Abstract: International audiencePredicting on circular domains is a central issue that can be addressed by Gaussian process (GP) regression. However, usual GP models do not take into account the geometry of the disk in their covariance structure (or kernel), which may be a drawback at least for industrial processes involving a rotation or a diffusion from the center of the disk. We introduce so-called polar GPs defined on the space of polar coordinates. Their kernels are obtained as a combination of a kernel for the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 21 publications
(34 reference statements)
0
29
0
Order By: Relevance
“…For , as we deal with angles, we cannot use a simple euclidean distance. When choosing the metric to use, we have to ensure that the resulting kernel is positive definite [ 34 , 35 ]. We can define two distance and based respectively on the chordal distance and the geodesic distance on : …”
Section: Msis Scan Mergingmentioning
confidence: 99%
See 1 more Smart Citation
“…For , as we deal with angles, we cannot use a simple euclidean distance. When choosing the metric to use, we have to ensure that the resulting kernel is positive definite [ 34 , 35 ]. We can define two distance and based respectively on the chordal distance and the geodesic distance on : …”
Section: Msis Scan Mergingmentioning
confidence: 99%
“…In [ 35 ], it is shown that for geodesic distance a -Wendland function [ 36 ] can be used to define a valid kernel …”
Section: Msis Scan Mergingmentioning
confidence: 99%
“…Two variants of tunnel Gaussian process (TGP) models are developed to elucidate aircraft's approach and landing dynamics, leveraging on the data recorded by advanced surface movement guidance and control system (A-SMGCS), which provides surveillance, routing, guidance for the control of vehicles and aircraft (see Section III.A, for details). TGP is developed by modifying and hybridizing sparse variational Gaussian process (SVGP) [24], which enables Gaussian process to handle big amount of data, and polar Gaussian process [25], which permits cylindrical coordinate modeling. The hybridization allows the proposed TGP to inherit the advantages of the two methods, to characterize and reveal the underlying probabilistic structure of approach and landing trajectory, and to provide interpretable tunnel views of the trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…For example Paciorek and Schervish (2006) create a new class of covariance functions (kernels) allowing the model to adapt itself to spatial surface whose variability changes with location. Likewise, Padonou and Roustant (2016) in a microelectronic framework define a GP model which inserts the geometry of the wafer in the kernel. That's why they introduce the polar GP defined with respect to polar coordinates: the covariance function is a sum of a product kernel of radius and a product kernel of polar angles.…”
Section: Introductionmentioning
confidence: 99%